Dynamics Reflect Gapless Edge Modes for Topological Superconductor. Issue 11 (25th September 2022) - Zhao, Xiaolong; Li, Ming; Qiu, Tianhui; Chen, Libo; Ma, Yulin; Ma, Hongyang; Yi, Xuexi
Abstract: The dynamical feature for a p ‐wave superconductor model in different parameter regions in terms of the appearance of topologically gapless edge modes in reel geometry is investigated. First, the parameter region with gapless edge modes versus a parameter and quasi‐momentum is shown. The parameter diagram can be reflected by the expectations of Pauli matrices in global manners. In another view, the dynamical feature of the excitation behave differently in the parameter regions with topological gapless edge modes and not. And the cusps of dynamical return rate vanish as the parameter pass the topological phase boundary slowly enough. It is found that the dynamics in the parameter region with gapless edge modes behaves differently to that without edge modes and related mostly to the eigenenergy gap between the pre‐and post‐quench eigenstates. The cusps of the dynamical return rate behave robustly against the noise occurs during evolution in the lattice until localization behavior dominates. This work benefits detecting topological edge modes by dynamical manners. Abstract : A parameter diagram in terms of the appearance of topological gapless edge modes for a topological superconductor is exhibited. Such a topological feature can also be reflected by the Pauli matrices and the dynamics in different aspects. But noise disturbs the dynamical features and leads to localization.